The role of institutional support on female-owned business sustainability from a developing Country’s perspective - Rogers Mwesigwa; Sarah Alupo; Mariam Nakate; Joseph Mayengo; Ruth Nabwami (Journal of Humanities and Applied Social Sciences, 2025)
Purpose – This study aims to examine the association between institutional support dimensions and female business sustainability in Uganda. Design/methodology/approach – This study adopted a cross-sectional and quantitative approach. We collected data from a sample of 224 female-owned businesses using a self-administered questionnaire. Findings – The findings indicate that institutional support is positively and significantly associated with the sustainability of female-owned businesses. The findings further indicate that all dimensions of institutional support (financial support, government policies and programs) are significantly and positively associated with female business sustainability. Research limitations/implications – This study employed a cross-sectional design; thus, it was impossible to monitor changes in the behavior of female-owned businesses over time. It may be possible to generalize the findings of this study to other developing countries. Originality/value – This study provides initial empirical evidence on the relationship between institutional support dimensions and female business sustainability using evidence from a developing African economy – Uganda.